An analysis of pest risk and potential economic impact of pine wilt disease to Pinus plantations in Australia. Issue 1 (2nd January 2018) - Carnegie, A. J.; Venn, T.; Lawson, S.; Nagel, M.; Wardlaw, T.; Cameron, N.; Last, I.
ABSTRACT: Pine wilt disease, caused by the Bursaphelenchus xylophilus (pinewood nematode), has caused extensive damage to Pinus forests where it has invaded countries with susceptible hosts and with co-occurring native species of the cerambycid beetle Monochamus . A pest risk analysis showed that there is a moderate likelihood of pinewood nematode and its primary vector, M. alternatus (Japanese pine sawyer beetle), arriving, establishing and spreading in Australia, and impacting Pinus plantations. Based on our climatic analysis, subtropical and Mediterranean climates in Australia are moderately-to-highly likely to be suitable for M. alternatus, but temperate regions may not be suitable. We present a scenario where pine wilt disease establishes in commercial Pinus plantations in south-east Queensland, spreads and causes significant tree mortality. The economic analysis suggested substantial losses in plantation timber revenue arising from tree mortality due to pine wilt disease, even at low probabilities of establishment and low rates of spread and mortality. For example, assuming chance of establishment is 5% y −1, spread rate is 1 km y −1, tree mortality rate is 20% and a 5% discount rate, the expected present value of plantation timber revenue losses in south-east Queensland is AU$6.9 million. This translates into high expected benefits from biosecurity programs, and indicates that it would be economically efficient to spend up to AU$0.345 million y −1 on biosecurity to keep pine wilt disease from establishing in south-east Queensland.